0360 Occupational exposure to respirable silica dust in men and women and risk for acute myocardial infarction. (21st August 2017) - Wiebert, Pernilla; Plato, Nils; Feychting, Maria; Sjögren, Bengt; Gustavsson, Annika; Andersson, Tomas; Gustavsson, Per
Abstract : Respirable silica dust is a common and serious occupational hazard to workers´ health. Inhalation causes inflammation which is a risk factor for cardiovascular disease, but few studies have confirmed a relationship. In the present study, we have investigated the risk of myocardial infarction in workers exposed to respirable silica dust, as well as differences in sensitivity based on gender. The cohort consists of manual workers in the Swedish National Census in 1980 with information on demography and occupation (1960–1990). Information on hospital admissions for acute myocardial infarction and cause of death were obtained from nation-wide registers. A job-exposure matrix was used to assess lifetime occupational exposure. No smoking data was available. Among manual workers ever exposed to respirable silica dust, the hazard ratio (HR) for acute myocardial infarction was 1.29 (95% Confidence Interval (CI) 1.15–1.46) for women, and 1.02 (95% CI 1.00–1.04) for men, respectively. In the highest quartile of cumulative exposure the HR was 1.66 (95% CI 1.27–2.18) for women, and 1.06 (95% CI 1.03–1.10) for men, respectively. We found a dose-response relationship between exposure and disease. The population etiologic fraction of disease for women was 11%. In absolute numbers this corresponds to 7 extra cases/10000 person years among exposed women in the highest exposed group. In conclusion, occupational exposure to respirable silica dust was in this study related to an increased risk for acute myocardial infarction in women, indicating a slightly increased sensitivity of the exposed women.